Preference Lecturers And Staffs In Conducting Self Medication - Trini Handayani (Fakultas Hukum Universitas Mataram, 2019)
Self-medication is one of the medication method in which it can cure the disease of a person in the absence of the need to expend much money and effort as well to visit a practitioner. Self-medication is literally a treatment that is performed by a person him/herself. An individual can actually purchase an Over The Counter medicine to treat their own disease. If it is done properly, self-medication can bring a huge advantage to the individual him/herself as they need, a medication state in which a person uses more than two medicines all at once. The focus of this research is to comprehend the behaviour of self-medication among the lecturers and staffs that are located in Suryakancana University. In order to conceive the behaviour of the respondents, a direct interview method is used by interviewing some of them. The interview result indicates that 96% respondens have performed self-medication at least once. In addition, there are several respondents admit that they have also performed polypharmacy. This also shows that the awareness regarding the correct type of medicine and the understanding of the indication written on the medicine is still relatively low among the lecturers and staffs